Pieśni wielkanocne z kancjonału radomskich bernardynów. Nieznane warianty tekstowe z rękopisu Biblioteki Diecezjalnej w Sandomierzu - Trościński, Grzegorz (Slavia Occidentalis, 2013)
The article is dedicated to anonymous 16th century religious Easter songs recorded in manuscript L 1684, which is part of the collection of the Diocese Library in Sandomierz. The manuscript, discovered by the article’s author, belonged to the Bernardine convent in Radom; parts of it were created in the second half of the 16th century, in the second half of the 17th century or in the early 18th century. The song Wszechmogący Ojca Najwyższego Syn Jezu Chryst is a mystery play song with references to religious Easter songs popular among the Bernardines, as well as songs included by Mikołaj from Wilkowieck in his mystery play, which revolves around motifs from the Scriptures and Biblical apocrypha. The song Chrystus Pan Zmartwychwstał includes diverse material where a text by Jakub Lubelczyk serves as a frame for the middle verses. The framework includes appellative prayers of the living for the dead (suffragia) from the 15th and 16th centuries, previously presented in the last part of ogurodzica. The discovered texts offer previously unknown variants of mystery songs and procession litanies.